Building a socially responsible higher education system in Latin America: Advances and challenges - Martí-Noguera, Juan José; Gaete Quezada, Ricardo (Education Policy Analysis Archives, 2019)
After one century of university reform in Córdoba, Argentina, the social responsibility of higher education institutions in Latin America is the subject of attention in this article. The higher education system and its role is analyzed through an interpretive-hermeneutic perspective, an analysis and interpretation of the growing number of legislations on the topic, as well as scientific articles that describe the main characteristics and conditions of social responsibility models that are developed and incorporated. In response to the impulses of a global system of higher education, which regulates supply and establishes quality parameters, the changes within Latin American higher education are discussed, as well as the impact that institutions can have on establishing the parameters of their social responsibility, so that they contribute to the response to the challenges within their regions.